2007
DOI: 10.1262/jrd.19014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the RNA Polymerase I-, II- and III-Dependent Transcript Levels Between Nuclear Transfer and In Vitro Fertilized Embryos at the Blastocyst Stage

Abstract: Abstract. Cloned animals have been produced in several mammalian species so far, although success rates to term are very low. Aberrations in gene expression derived from abnormal epigenetic status have been thought to be a cause of developmental abnormalities in clones, and several abnormalities in gene expression have already been detected in cloned animals and embryos. In this study, we examined the hypothesis that the poor survival rates of nuclear transfer (NT) embryos are partly due to aberrations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Lastly, we have verified that the synthesis of rRNAs is not affected in spermatid-derived embryos. Indeed, in mouse, defect in rRNA synthesis has been proposed to explain the developmental defect of nuclear transfer embryos (Suzuki et al 2007;Zheng et al 2012) and could explain the difference in the bulk of RNA synthesis observed between sperm-and spermatid-derived embryos (Bui et al 2011). We observed that newly synthesized 18S and 28S rRNAs are equally well produced in sperm-and spermatid-derived embryos (Supplemental Fig.…”
Section: Developmentally Important Genes Are Misregulated In Spermatisupporting
confidence: 51%
See 2 more Smart Citations
“…Lastly, we have verified that the synthesis of rRNAs is not affected in spermatid-derived embryos. Indeed, in mouse, defect in rRNA synthesis has been proposed to explain the developmental defect of nuclear transfer embryos (Suzuki et al 2007;Zheng et al 2012) and could explain the difference in the bulk of RNA synthesis observed between sperm-and spermatid-derived embryos (Bui et al 2011). We observed that newly synthesized 18S and 28S rRNAs are equally well produced in sperm-and spermatid-derived embryos (Supplemental Fig.…”
Section: Developmentally Important Genes Are Misregulated In Spermatisupporting
confidence: 51%
“…Several hypotheses were proposed to explain the nature of this programming, including the idea that sperm is programmed for efficient replication after fertilization (Lemaitre et al 2005) or for supporting proper embryonic transcription (Suzuki et al 2007;Hammoud et al 2009;Zheng et al 2012). The latter hypothesis was proposed following the observation that promoters of developmentally important genes escape global replacement of histones by protamines in mature sperm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been reported previously between mouse in vitro fertilization and tail tip cell NT embryos. The author believed that, in NT blastocyst, the accumulation unprocessed 47 S rRNA and rRNA intermediates failed to be processed into mature rRNAs (31). Because no significant differences were found in FBL and B23 expressions between ICSI and NT groups in our study, the exact mechanism might be more complicated and need further investigations.…”
Section: Discussionmentioning
confidence: 61%
“…qPCR reactions were performed based on 1.5 l of cDNA sample, 10 l of TransStart TM Top Green qPCR SuperMix (TransGen, AQ131), and gene-specific primers (supplemental Table 1) in a 20-l reaction system on CFX96 Realtime System (Bio-Rad). H2afz, Hprt1, and Exno TM were used as candidate references for embryos (31,32). HP1␥, cyclophilin-A, and cyclophilin-B were used as candidate references for cells (13).…”
Section: Methodsmentioning
confidence: 99%